Effects of a high‐intensity functional exercise program on depressive symptoms among people with dementia in residential care: a randomized controlled trial. (7th December 2015) - Boström, Gustaf; Conradsson, Mia; Hörnsten, Carl; Rosendahl, Erik; Lindelöf, Nina; Holmberg, Henrik; Nordström, Peter; Gustafson, Yngve; Littbrand, Håkan
Abstract : Objectives: The aim of this study is to evaluate the effect of a high‐intensity functional exercise program on depressive symptoms among older care facility residents with dementia. Methods: Residents ( n = 186) with a diagnosis of dementia, age ≥ 65 years, Mini‐Mental State Examination score ≥ 10, and dependence in activities of daily living were included. Participants were randomized to a high‐intensity functional exercise program or a non‐exercise control activity conducted 45 min every other weekday for 4 months. The 15‐item Geriatric Depression Scale (GDS) and the Montgomery–Åsberg Depression Rating Scale (MADRS) were administered by blinded assessors at baseline, 4, and 7 months. Results: No difference between the exercise and control activity was found in GDS or MADRS score at 4 or 7 months. Among participants with GDS scores ≥ 5, reductions in GDS score were observed in the exercise and control groups at 4 months (–1.58, P = 0.001 and –1.54, P = 0.004) and 7 months (–1.25, P = 0.01 and –1.45, P = 0.007). Among participants with MADRS scores ≥ 7, a reduction in MADRS score was observed at 4 months in the control group (–2.80, P = 0.009) and at 7 months in the exercise and control groups (–3.17, P = 0.003 and –3.34, P = 0.002). Conclusions: A 4‐month high‐intensity functional exercise program has no superior effect on depressive symptoms relative to a control activity among older people with dementia living in residential care facilities. Exercise and non‐exercise group activities may reduce high levels of depressive symptoms.